2022
DOI: 10.3389/fphar.2022.862831
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Horizon of Graves’ Hyperthyroidism: Treatment Regimens Based on Immunology and Ingredients From Traditional Chinese Medicine

Abstract: Graves’ disease is an autoimmune disease characterized by goiter and hyperthyroidism, and 25% patients develop GO. Traditional treatment options, such as antithyroid drugs, radioiodine or thyroidectomy, have remained largely unchanged over the past 70 years. For many patients, there is a high rate of recurrence after antithyroid drugs and lifelong hypothyroidism after ablation and thyroidectomy. The symptoms and quality of life of some patients have not been effectively improved. The clinical demand for new th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 111 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…A study has shown that herbal medicine is an effective alternative for the treatment of hyperthyroidism due to Graves' disease, especially in patients with an allergy to thionamide [ 36 ]. When used as an adjunctive medicine, the active ingredients of herbal medicine are not only effective in relieving goitre, Graves' ophthalmopathy symptoms, and hypermetabolic symptoms but also in reducing the side effects and allergic symptoms of antithyroid drugs and in increasing the dose of ATD in allergic patients [ 37 ]. There is now a need to expand the understanding of how Chinese medicine can help in the treatment of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that herbal medicine is an effective alternative for the treatment of hyperthyroidism due to Graves' disease, especially in patients with an allergy to thionamide [ 36 ]. When used as an adjunctive medicine, the active ingredients of herbal medicine are not only effective in relieving goitre, Graves' ophthalmopathy symptoms, and hypermetabolic symptoms but also in reducing the side effects and allergic symptoms of antithyroid drugs and in increasing the dose of ATD in allergic patients [ 37 ]. There is now a need to expand the understanding of how Chinese medicine can help in the treatment of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it would be optimal to conduct serum selenium testing prior to commencing supplementation in order to prevent potential overdose ( 33 ). Additionally, extensive research has been conducted on the efficacy of various Chinese medicines in ameliorating symptoms and signs associated with GD, as well as expediting the treatment process ( 34 , 35 ). Such as: Diosgenin (Dio) had control effects on goiter and hyperthyroidism in GD mice through affecting thyroid cell proliferation, but not the expression of TRAB ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICRN (C 33 H 40 O 15 , M w = 676.67) is a type of prenylated flavonoid, showing extensive bioactivities such as antioxidant [ 44 , 45 , 46 , 47 ], neuroprotective [ 48 , 49 , 50 , 51 , 52 ], and antitumor [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] behavior as well as anti-inflammatory responses [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and can be used to treat erectile dysfunction [ 69 , 70 , 71 , 72 ]. It appears it can improve the function of organs including bones and the heart [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%